The effect of somatotype characteristics of athletes on the balance performance - Top, E.; Celenk, C.; Marangoz, I.; Aktug, Z.; Yilmaz, T.; Akil, M. (Journal of Education and Learning, 2018)
Our study aims to investigate the effects of somatotype characteristics of elite athletes on the balance performances. The study has included 46 elite athletes totally. The heights, body weights, skinfold thicknesses, periphery and diameter of skinfold of the subjects included in the study have been measured and somatotype characteristics have been determined by using Heath-Carter method. The balance performances of the athletes have been evaluated by using Biodex Balance System. It has been determined that the dynamic balance performance of the athletes has changed in accordance with the endomorph, mesomorph and ectomorph characteristics of the athletes; however, static balance performances have not changed. Accordingly, no difference has been observed between the oscillation indexes and static balances of the athletes (p>0.05), whereas a significant difference has been found as the balance level increases in accordance with the endomorph, mesomorph and ectomorph characteristics of the athletes in terms of dynamic balances (p<0.01, p<0.05, p<0.001). In conclusion, it is assumed that the athletes having endomorphic characteristics may be more successful in the sports branches that put an emphasis on the balance.